Analisis Faktor Risiko Penggunaan Kelambu, Penggunaan Obat Anti Nyamuk, Kebiasaan Keluar Rumah dan Keberadaan Tempat Perindukan Nyamuk Terhadap Kejadian Malaria di Indonesia Meta Analysis Tahun 2012-2022 - Qatrunnada Ramadhani, Nadhifah; R Azizah; Sulistyorini, Lilis; Eka Ramadhan, Gaung (STIKES Ngesti Waluyo, 2024)
Malaria is a disease caused by the Plasmodium parasite, with the first symptoms being fever, headache, and chills, usually appearing 10-15 days after an infective mosquito bite and may be mild and difficult to recognize as malaria. Plasmodium parasite, which is transmitted to humans through the bite of an infected female Anopheles mosquito. There are five species of parasites that cause malaria in humans; 2 of these species are P. falciparum and P. vivax – posing the greatest threat. P. falciparum is the deadliest malaria parasite and is most commonly found on the African continent, while P. vivax is the dominant malaria parasite in most countries outside sub-Saharan Africa. This research aims to analyze the risk factors that influence the use of mosquito nets, the use of anti-mosquito medication, the habit of leaving the house, and the existence of mosquito breeding sites on the incidence of malaria in Indonesia. The method in this research uses meta-analysis, which is a statistical method that combines several research results quantitatively by looking for effect size or summary values using JASP software version 0.16.4. The data source in this research comes from Google Scholar, and sorting was carried out according to the inclusion-exclusion criteria. Fourteen research articles were obtained. The results of secondary data from the meta-analysis method showed that the variable using mosquito nets had a risk 2.013 times greater, the variable using anti-mosquito medication had a risk 2.915 times greater, the variable habit of going out of the house had a risk 2.886 times greater, and the variable the existence of a nesting place had a risk 3.560 times Indonesia has a greater incidence of malaria. The conclusion from the results of the meta-analysis is that there is the greatest level of risk for the incidence of malaria in Indonesia; the variable is the existence of mosquito breeding places, the use of mosquito repellent, the habit of leaving the house, and the lowest variable is the use of mosquito nets. Efforts to control the risk of malaria in Indonesia include using mosquito nets when sleeping, using mosquito repellent, reducing activities outside the home at night, and cleaning mosquito breeding areas around the house.